THE SIGNIFICANCE OF METABOLIC SYNDROME AND NUTRITION IN PATIENTS WITH CHRONIC HEPATITIS - Jalolov N. N.; Izzatillayeva Y. F. (American Journals Publishing, 2026)
Chronic hepatitis represents a major global public health challenge, and its course and progression are significantly influenced by metabolic syndrome and nutritional factors. According to the World Health Organization (WHO), more than 300 million people worldwide live with chronic hepatitis B infection, and over 50 million with chronic hepatitis C infection. At the same time, the global prevalence of metabolic syndrome is estimated at approximately 25–30%, reaching up to 40% in certain populations. Scientific evidence indicates that key components of metabolic syndrome—insulin resistance, abdominal obesity, dyslipidemia, and arterial hypertension—accelerate liver fibrosis progression and increase the risk of steatosis and cirrhosis in patients with chronic hepatitis. Dietary patterns, particularly high-calorie regimens rich in saturated fats, further exacerbate hepatocellular injury.
Keywords: Chronic hepatitis, metabolic syndrome, insulin resistance, hepatic steatosis, fibrosis, nutrition, diet therapy